Exploring the Link Between Food Security, Health Services, and Family Income on Wasting Incidence Among Toddlers (0-59 Months) - Alam, Syamsul; Harun, Iriyanti; Nurfatmi, Rezki (Diversity: Disease Preventive of Research Integrity, 2024)
Wasting remains a significant nutritional challenge in Indonesia. Despite a reduction in its prevalence from 10.2% in 2018 to 7.1% in 2021, the rate still falls short of the national target of 7%. This study aims to examine the relationship between health services and family income on the incidence of wasting in toddlers aged 0-59 months in the Polombangkeng Utara sub-district, Takalar district. The research employed a quantitative approach with a cross-sectional study design. The population in this study consisted of toddlers aged 0-59 months in the North Polombangkeng sub-district, with a sample size of 146 toddlers. A probability sampling technique was used. The analysis was conducted using the chi-square test. The results of the chi-square test show that household food security is not related to the incidence of wasting, with a p-value of 0.590 (>0.05). Similarly, there is no relationship between growth monitoring and the incidence of wasting, with a p-value of 0.240 (>0.05), and no relationship between the completeness of immunization status and the incidence of wasting, with a p-value of 0.776 (>0.05). However, family income does show a relationship to the incidence of wasting, with a p-value of 0.032 (<0.05). This study indicates that food security and health services do not impact the incidence of wasting. In contrast, family income, which is a primary factor in nutritional problems, does have an impact on the incidence of wasting. The issue of wasting in toddlers can be prevented and addressed through specific and sensitive nutrition interventions.